A Gedenkschrift to Randy Hodson Working with Dignity. - Lisa A Keister; Vincent J Roscigno (Research in the Sociology of Work,, 2016)
Randy Hodson was one of contemporary sociology's central figures in the study of work, occupations, and inequality. This volume pays tribute to his important scholarly contributions. Chapters by other important scholars in these fields reflect and build on his research in work conditions, worker resistance, and social stratification.